Comprehensive Evaluation of Thyroid Gland Volume in Relation to Sex, Age and Body Surface Area among Bangladeshi Population - Lina, Roksana Shirin; Alim, Noor E Amrin; Bhowmick, Baishakhi; Islam, Shehrin; Yesmin, Nadia; Sultana, Abeda; Tasnim, Sabrina (IAHS Medical Journal, 2026)
Background: Thyroid gland morphometry, with a focus on volume, is a crucial and highly valuable metric in clinical practice. Ultrasonography can easily access the thyroid gland. This study aimed to appraise the normal thyroid gland volume in relation to sex, age and Body Surface Area (BSA) among Bangladeshi population of Chattogram district. Materials and methods: This cross-sectional study evaluated total thyroid gland volume of 200 (100 male, 100 female) Bangladeshi population of Chattogram district. It was conducted in the department of Anatomy, Chittagong Medical College, during July 2022-June 2023. Thyroid ultrasound was conducted by expert sonologists. The statistical analysis was done using SPSS version 26 and at 95% level of significance, p-value was considered significant if it was <0.05. Results: Total thyroid gland volume (Range: 3.87±1.63 to 3.02±0.93 ml) decreased from third to fourth decade and also from fifth to sixth decade. For the various age groups, the mean of total thyroid gland volume was not different significantly (p> 0.05). In male, the total thyroid gland volume was greater than in female and this was highly significant statistically (p=0.000) Spearman’s correlation test revealed that total thyroid gland volume was positively correlated with BSA (p=0.000). Conclusion: Result of the present study offers a normative reference data regarding normal thyroid gland volume of Bangladeshi population to help the clinicians and surgeons to deal with numerous thyroid pathologies. IAHS Medical Journal Vol 8(1), June 2025; 83-87